2D Animation Video of IoT-Based Agricultural Monitoring Using Onion Skinning Technique - Armando Munazdar; Mohamed Nur (Journal of Multimedia Trend and Technology, 2023)
Learning is support from educators to help students acquire knowledge, skills and habits, as well as carry out the process of forming attitudes and beliefs. In other words, learning is a process that helps students learn well. Learning has the same meaning as teaching, but has a different meaning. In education, educators teach students to study and master the content of the material in order to achieve certain goals (cognitive aspects), changes in students' attitudes (emotional aspects) and skills (psychological aspects) can also affect students. After the outbreak of COVID19 in Indonesia, the learning process between educators and students was changed through e-learning. The application of e-learning makes the practicum process less effective, especially the practical learning of IoT (Internet of Things). Often, students struggle to understand what materials to use and what materials to design first when it comes to IoT tools. For this reason, we need a learning media that can help students understand the function and design of IoT tools. The purpose of making teaching aids in the form of animated videos is so that students can understand what materials are used and also pre-engineering IoT devices. The method used in designing this learning animation video is MDLC which consists of three stages, namely pre-production, production, and post-production. The results of this study are that a learning animation video has been successfully made about IoT tools.